Antiretroviral Therapy and Periarticular Osteonecrosis Development in Patients With HIV. Issue 3 (1st February 2023) - Bahoravitch, Tyler J.; Agarwal, Amil; Ifarraguerri, Anna M.; Howard, Peter; Srikumaran, Uma; Thakkar, Savyasachi
Abstract : Introduction: With modern antiretroviral therapy (ART), HIV has become a chronic condition. Previous studies have not definitively assessed the risk of periarticular osteonecrosis (ON) that ART poses to the HIV population. Methods: A retrospective case-control study using the PearlDiver database was done using International Classification of Diseases codes. Patients were selected from 2010 to 2019 with a diagnosis of periarticular ON and HIV taking ART (HIV+/ART+) and not taking ART (HIV+/ART−). The control was patients HIV− and not on ART. Subcategorization, by International Classification of Diseases codes, was used for which joint was affected—hip, knee, or shoulder—excluding patients with ON of the jaw. Chi-squared univariate analysis was used to compare incidence rates and control for age, sex, Elixhauser comorbidities, and other known risk factors for developing ON in multivariable analysis. Results: In total, 219, 853 patients had HIV between 2010 and 2019. Of those patients, 123, 710 (56.27%) had a history of ART (HIV+/ART+), while 96, 143 (43.74%) did not (HIV+/ART−). Difference in incidence rates for HIV+/ART+ was higher in any joint (+1.7%), as well as the hip (+1.31%), knee (+0.08%), and shoulder (+0.08%). All risk factors met inclusion criteria in the multivariate analysis except coagulopathy. Multivariate analysis found that patients in the HIV+/ART+ cohort had higher odds of developing periarticular ON when compared with the HIV+/ART− cohort in any joint (odds ratios = 1.40; 95% CI, 1.38 to 1.42), hip (OR:1.41; 95% CI, 1.38-1.43), knee (OR:2.56; 95% CI, 2.39 to 2.74), and shoulder (OR:1.05; 95% CI, 1.01-1.10). Conclusion: Patients with HIV taking ART have well-established morbidity and mortality benefits. However, this study found that ART is associated with a higher risk of developing periarticular ON when compared with those not taking ART. Therefore, clinicians should be hypervigilant of patients on ART and their risk of ON, especially asymptomatic patients, and focus on modifiable risk factors and early surgical correction. Level of Evidence: III